MODERASI BERAGAMA SEBAGAI INSTRUMEN PERLINDUNGAN HAK KEBEBASAN BERAGAMA DAN BERKEYAKINAN - Wawan Saputra (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2025)
This research discusses religious moderation as an instrument for protecting the right to freedom of religion and belief in Indonesia. Freedom of religion and belief is a constitutional right and a human right guaranteed by the 1945 Constitution of the Republic of Indonesia as well as various international legal instruments. However, in practice, various forms of intolerance, discrimination, rejection of places of worship, and religion-based violence that threaten the protection of these rights are still found. This study aims to analyze the role of religious moderation in strengthening the protection of freedom of religion and belief and to identify the challenges of its implementation in a multicultural society. The research method employed is normative legal research using legislative, conceptual, and human rights approaches. The findings indicate that religious moderation plays a strategic role in fostering tolerance, preventing extremism, and creating a harmonious and inclusive social life. Religious moderation must be strengthened through education, law enforcement, interfaith dialogue, and state policies oriented toward the protection of human rights. Thus, religious moderation can serve as an effective instrument in safeguarding democracy, national unity, and the protection of the right to freedom of religion and belief in Indonesia.